La memoria sociale dei Beoti: una prospettiva senza Atene - Tufano, Salvatore (Histos, 2019)
The paper investigates a selection of fragments of Boeotian local historiography. The main goal is to re-evaluate the weight of this genre in the reconstruction of the history of the region. The first section (1) argues for the necessity to reconsider local historiography as a fundamental source in writing a regional history of the Greek world: a state of the art is summarised and an updated picture of the genre is presented. In the second (2), a critical anthology uses three categories (lieux de mémoire; cults; local time) to shed new light on the meaning of Boeotian local historiography and argue for its originality.